MODERNIZATION OF THE THREE-CYCLE ENGINEERING EDUCATION BASED ON FSES 3++ AND CDIO++ - A. I. Chuchalin (Высшее образование в России)
The paper proposes an approach to modernization of engineering programs at three cycles of higher education (bachelor, master, doctor) based on the CDIO++ Standards developed in Russia in the conditions of transferring to a new version of the Federal State Educational Standards (FSES 3++). The CDIO++ Standards are represented by a CDIO-FCDI-FFCD triad taking into account the differences between complex, innovative and research engineering activity. The peculiarity of the three-cycle engineering programs design based on the CDIO++ Standards is that program objectives and outcomes are defined considering the graduate training programs focus on various types of engineering activity at various stages of engineering products, processes and systems lifecycle. The modular structure of the programs is formed according to the FSES 3++ requirements. Each program module should contribute to achievement of the intended program outcomes. The program content, teaching and learning technologies, as well as the conditions of program delivery should meet the FSES 3++ and CDIO++ requirements. The developed approach is used being implemented in the Kuban State Technological University and is recommended to be used in other Russian universities, first and foremost in those participating in the “Worldwide CDIO++ Initiative”, as well as leading universities participating in the “5-100” programme aiming at preparation of academic and teaching staff (masters and doctors).